2021
DOI: 10.3390/polym13040483
|View full text |Cite
|
Sign up to set email alerts
|

An Optimum Fatigue Design of Polymer Composite Compressed Natural Gas Tank Using Hybrid Finite Element-Response Surface Methods

Abstract: The main purpose of this research is to design a high-fatigue performance hoop wrapped compressed natural gas (CNG) composite cylinder. To this end, an optimization algorithm was presented as a combination of finite element simulation (FES) and response surface analysis (RSA). The geometrical model was prepared as a variable wall-thickness following the experimental measurements. Next, transient dynamic analysis was performed subjected to the refueling process, including the minimum and maximum internal pressu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…Several polymeric materials (such as acrylonitrile butadiene styrene (ABS), polylactic acid (PLA), nylon (PA6), polypropylene (PP), polyether ether ketone (PEEK), low-density polyethylene (LDPE), high-density polyethylene (HDPE), etc.) have been used for numerous industrial and prototyping applications [ 6 , 7 , 8 , 9 , 10 ] on the FDM printing platform and are easily available in standard sizes on the commercial market. The commercially available materials have a major constraint in that they cannot exhibit all the desirable properties in one single material.…”
Section: Introductionmentioning
confidence: 99%
“…Several polymeric materials (such as acrylonitrile butadiene styrene (ABS), polylactic acid (PLA), nylon (PA6), polypropylene (PP), polyether ether ketone (PEEK), low-density polyethylene (LDPE), high-density polyethylene (HDPE), etc.) have been used for numerous industrial and prototyping applications [ 6 , 7 , 8 , 9 , 10 ] on the FDM printing platform and are easily available in standard sizes on the commercial market. The commercially available materials have a major constraint in that they cannot exhibit all the desirable properties in one single material.…”
Section: Introductionmentioning
confidence: 99%
“…The application area for the material and design-specific FDM-printed parts has also seen strong growth. Various studies in past have reported mechanical- and morphological-specific improvement of FDM-printed parts when the parts are post-processed by selecting the suitable route [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Unlike isotropic materials, the FRP composite tubes are made with different fibre volume fractions, and it makes it more complex to predict the behaviour of a different component. Prediction of the damage mechanism of a composite structure is a difficult procedure and it requires several experimental tests to predict the structural behaviour after failure [ 37 , 38 ]. For time and cost reduction, the FE method is a vital tool to realize the full-scale model behaviour before the production stage.…”
Section: Introductionmentioning
confidence: 99%